Hubungan antara kejadian delirium dengan anemia pada pasien geriatri di bangsal rawat inap geriatri RSUP sanglah - Shelvy Florence Gousario; RA Tuty Kuswardhani (Intisari Sains Medis, 2020)
Background: Delirium is common, occurs in 20% to 79% of hospitalized older patients. It has been associated with increased health care costs, long-term cognition deficits, and increase mortality. Anemia has been noted as one of predisposing factors for delirium. Elderly patients with many risk factors will be vulnerable to a low level precipitating insult, whereas those without risk factors may only become delirious after a high level insult. The objective of this study was to find association between delirium status and anemia among elderly patients.Method: cross-sectional design using analytic observational was conducted with purposive sampling. Total subject of this study was one hundred and sixteen elderly patients, taken at geriatric ward Sanglah general hospital from January to May 2016. Delirium status was screened using Confusion Assessment Method (CAM). Assessment of delirium was confirmed if meet the criteria acute, fluctuating onset an inattention, plus disorganized thinking and/or changes in consciousness. Anemia was defined as level of serum hemoglobin < 10 g/dL. Statistical analysis used was chi square comparative test .Results: One hundred and sixteen elderly patients age 60 to 95 years old with mean 72.16 + 8.179 were included. The prevalence of delirium and anemia were 28 (24.1%) and 40 (34.5%) respectively. We found significant association between delirium status and anemia (p= 0.034).Conclusion: there was significant association between delirium status and anemia among elderly patients at geriatric ward Sanglah general hospital.Â Pendahuluan: Delirium merupakan suatu keadaan yang sering terjadi pada 20 hingga 70% pasien geriatri yang menjalani rawat inap. Keadaan ini dihubungkan dengan peningkatan biaya kesehatan, defisit kognitif jangka panjang, serta peningkatan mortalitas. Anemia telah diketahui sebagai salah satu faktor predisposisi terjadinya delirium. Pasien geriatri dengan banyak faktor risiko akan lebih rentan terhadap jejas yang kadarnya rendah. Penelitian ini bertujuan untuk mengetahui hubungan antara delirium dan anemia pada pasien geriatri.Metode: penelitian ini merupakan penelitian observasional dengan rancangan potong lintang analitik menggunakan consecutive sampling. Subjek dalam penelitian ini berjumlah 116 pasien yang berasal dari bangsal rawat inap geriatri RSUP Sanglah Denpasar pada Januari hingga Mei 2016. Delirium dievaluasi menggunakan metode CAM (Confusion Assessment Method). Anemia didefenisikan sebagai kadar hemoglobin serum <10 g/dL. Analisa statistik menggunakan uji komparatif chi-square.Hasil: Dari 116 pasien yang menjadi sampel dalam penelitian ini, didapatkan rata-rata umur 72,16 + 8,179 dengan umur terendah 65 tahun dan tertinggi 95 tahun. Prevalensi delirium dan anemia sebesar 28 (24,1%) dan 40 (34,5%) berturut-turut. Didapatkan adanya hubungan yang bermakna antara kejadian delirium dengan anemia (p= 0,034)Kesimpulan: Ada hubungan yang bermakna antara kejadian delirium dengan anemia pada pasien-pasien geriatri di bangsal rawat inap geriatri RSUP Sanglah Denpasar.